COMPLEX-FORMING ADSORBENTS BASED ON KAOLINITE, ALUMINIUM OXIDE AND POLYPHOSPHATES FOR THE EXTRACTION AND CONCENTRATION OF HEAVY METALS IONS FROM WATER SOLUTIONS - Tarasevich Yu.I.; Klimova G.M. (My University, 2001)
The sorbents for the absorption of heavy metal ions from water solutions are developed by the modification of kaolinite, meta-kaolinite and aluminium oxyhydride by polyphosphates. It is shown that for sorption from concentrated solutions, the amount of the polyphosphate inoculated to the sorbent due to the condensation reaction significantly exceeds the number of anionic exchange sites existing at the surface of the sorbent. The adsorption isotherms of Ni2+, Co2+ and Cr3+ at the adsorbents prepared in this way demonstrate high adsorption capacity (300 to 100 mg/g depending on the sorbent type) and high selectivity of the materials with respect to the sorbed cations. The distribution coefficients in the Henry region, Kd=5·105–1·104 cm3/g, are comparable to the values characteristic to organic chelate-forming sorbents. Electron reflection spectra are indicative of the complex-forming mechanism of the adsorption of Ni2+, Co2+ and Cr3+ at the modified adsorbents. The decrease of pH to 2 results in the almost complete desorption of heavy metal ions from the adsorbent surface. The method that involves the use of aluminium oxynitrate is developed for the preparation of mechanically strong water-resistant hydrostable granules of modified sorbents. The sorbents were tested in the process of Ni2+ removal from galvanic wastewater; the concentration of these ions was decreased from 200 to 0.5 mg/dm3.